Accurate Prediction of Tissue Viability at Postoperative Day 7 Using Only Two Intraoperative Subsecond Near-Infrared Fluorescence Images. Issue 2 (February 2017) - Wada, Hideyuki; Vargas, Christina R.; Angelo, Joseph; Faulkner-Jones, Beverly; Paul, Marek A.; Ho, Olivia A.; Lee, Bernard T.; Frangioni, John V.
Abstract : Background: The ability to predict the future viability of tissue while still in the operating room and able to intervene would have a major impact on patient outcome. Although several objective methods to evaluate tissue perfusion have been reported, none to date has sufficient accuracy. Methods: In eight Sprague-Dawley rats, reverse McFarlane dorsal skin flaps were created. Continuous near-infrared fluorescence angiography using indocyanine green was performed immediately after surgery, for a total of 30 minutes. These dynamic measurements were used to quantify indocyanine green biodistribution and clearance, and to develop a simple metric that accurately predicted tissue viability at postoperative day 7. The new metric was compared to previously described metrics. Results: Reproducible patterns of indocyanine green biodistribution and clearance from the flap permitted quantitative metrics to be developed for predicting flap viability at postoperative day 7. Previously described metrics, which set the boundary between healthy and necrotic tissue as either 17 or 25 percent of peak near-infrared fluorescence at 2 minutes after indocyanine green injection, underestimated the area of necrosis by 75 and 48 percent, respectively. Our data suggest that both the shape and area of clinical necrosis occurring at postoperative day 7 can be predicted intraoperatively, with the boundary defined as near-infrared fluorescence intensities of 40 to 55 percent of peak fluorescence measured at 5 minutes. Conclusion: Two 750-msec intraoperative near-infrared fluorescence images obtained at time 0 and at 5 minutes after injection of indocyanine green accurately predicted skin flap viability 7 days after surgery. Abstract : Supplemental Digital Content is available in the text.